Transregionalization in the Context of Globalization - D. A. Kuznetsov (Vestnik MGIMO-Universiteta, 2021)
Transregionalization has already become a powerful trend in world politics. States and regional associations employ transregional initiatives to realize their own and collective interests. This new level of international interaction embraces a wide range of actors and fosters interconnectedness based on geographical proximity but shared functional preferences. Given the opposition between isolationism and disintegration, there is a problem of the relation between transregionalization and globalization. If the processes are unidirectional, then transregionalization is a stage of globalization. If they contradict each other, transregionalization facilitates the creation of new dividing lines.Considering several cases of megaprojects, especially in the Asia-Pacific, the article substantiates the typology of transregionalization, emphasizing its cooperative (inclusive and aimed at global integration) and competitive form (mostly exclusive and impossible to converge with other projects). The author stresses that strengthening functional ties makes transregionalization an adaptive version of globalization driven by common interests and shared views of future global development paths. Intensification of transregional relations is likely to stimulate globalization and integration practices and the participation of state and nonstate actors in global governance.In today’s world politics, transregionalization exists mainly in the form of projects and initiatives. This signifies both difficulties in reaching consensus on further cooperation and conservative states’ policy towards participating in such large-scale associations. However, the very emergence of transregional associations with varying degrees of convergence and institutionalization, promoting specific institutional and economic development and cooperation patterns, strengthens multipolarity of the international system.